PENGGUNAAN SOFTWARE BAJAKAN DI LEMBAGA KEUANGAN SYARIAH DALAM PERSPEKTIF KEPEMILIKAN ISLAM - Muqorobin, Ahmad; Achsani, Realis Fachry (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The development of computer technology plays an important role in every human activity in this era of globalization. In case of using a computer then close relation with the name of the software. However, by the high price of a software license and the lack of public knowledge regarding the software license makes some people use pirated software, one of them is Baitul Maal Wat Tamwil (BMT). The purpose of this study is to examines the problem of pirated software use in Islamic Finance Institutions from the perspective of Shariah, i.e. be in Baitul Maal Wat Tamwil (BMT). This research with descriptive-inductive method analyzed the problems and circumstances at the filed by using the data from observation and interview results. So those analyzing result can be concluded with deductive method. From the results of this research, it can be concluded that Software is seen as property, in this case it was included as a perfect ownership (Milku Tam). Doubling that occurs in BMT Surya Mandiri is a violation of the rights of the Creator who has Perfect Ownership (Milku Tam) and the creator has the right to deprive others of abusing his creation. This is obviously detrimental to the creator, because economic value contained in his creation into nothing and this is tantamount to taking the property of others.